Social work in the "my best years" program of the Ministry of Economic and Social Inclusion (MIES) - Alava Barreiro, Leila Maria (2020)
In the framework of global changes, Ecuador, through its 2008 Constitution, recognizes older adults as a group of priority care, which implies guaranteeing their rights through specialized care in both the public and private spheres, which is why The objective of this research was to characterize the role of the social worker in the MIES "My Best Years" Program in the San Sebastián parish of the Pichincha canton, Manabí province. In which we worked with 75 elderly beneficiaries of the "My best years" Program. The realization of this study was based on non-experimental research, the descriptive-exploratory, bibliographic and statistical methods were used, which allowed the information obtained to be processed, in the same way the interview technique applied to the worker was applied. responsible for executing this program in the parish. As results, the essential work of the professional in the application of instruments that allow early detection of problems in the elderly is highlighted. To conclude this program, they allow the elderly to improve their vulnerability, reducing the stereotypes that society imposes on people over 65, expanding the coverage of access to relevant services for this population group.